2018
DOI: 10.1016/j.virusres.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mwinilunga alphavirus: A novel alphavirus in Culex mosquitoes in Zambia

Abstract: Mosquito-borne alphaviruses are disseminated globally and cause febrile illness in humans and animals. Since the prevalence and diversity of alphaviruses has not been previously investigated in Zambia, reverse transcription PCR was employed as a broad-spectrum approach for the detection of alphaviruses in mosquitoes. From 552 mosquito pools, a novel alphavirus, tentatively named Mwinilunga alphavirus (MWAV), was discovered from a single Culex quinquefasciatus mosquito pool. The full genome of MWAV was subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…To investigate the vector of YYV, the assembled contigs were compared to a cytochrome oxidase I (COI) database of Australian mosquito species (17) using BLASTn v2.9.0ϩ (18) with an E value cutoff of 10 Ϫ5 , and the results were filtered for alignments Ͼ200 bp in length and matches of Ͼ95% identity. Only two mosquito species were present in all three traps, Anopheles annulipes and Culex australicus/Culex globocoxitus (these two Culex species are indistinguishable using COI), supporting previous studies that have detected mosquito-specific alphaviruses from only Anopheles and Culex species (2)(3)(4)(5). Due to the homogenization of the traps, the YYV vector species cannot be definitively determined.…”
supporting
confidence: 67%
“…To investigate the vector of YYV, the assembled contigs were compared to a cytochrome oxidase I (COI) database of Australian mosquito species (17) using BLASTn v2.9.0ϩ (18) with an E value cutoff of 10 Ϫ5 , and the results were filtered for alignments Ͼ200 bp in length and matches of Ͼ95% identity. Only two mosquito species were present in all three traps, Anopheles annulipes and Culex australicus/Culex globocoxitus (these two Culex species are indistinguishable using COI), supporting previous studies that have detected mosquito-specific alphaviruses from only Anopheles and Culex species (2)(3)(4)(5). Due to the homogenization of the traps, the YYV vector species cannot be definitively determined.…”
supporting
confidence: 67%
“…Recently, antibodies specific to ZIKV were also detected in non-human primates in Zambia [29]. Furthermore, our mosquito surveillance studies have shown that the first evidence of the circulation of WNV and the existence of a novel alphavirus in Zambia [30,31].…”
Section: Introductionmentioning
confidence: 80%
“…The group contains three insect-restricted alphaviruses that have been detected in mosquitoes from the Old World [ 2, 3, 11 ]. These viruses, Eilat virus (EILV), Taï Forest alphavirus (TALV) and Mwinilunga alphavirus (MWAV), form a monophyletic sister clade to the WEE complex [ 3, 11 ]. TALV and MWAV could not be isolated in cell culture.…”
Section: Introductionmentioning
confidence: 99%